Phenytoin induced toxic epidermal necrolysis: a case report - Barkakaty, Sandipan; K., Girish (International Journal of Basic & Clinical Pharmacology, 2019)
Stevens Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), are severe idiosyncratic reactions characterized by fever and mucocutaneous lesions leading to necrosis and sloughing of the epidermis. The usage of anticonvulsants like carbamazepine, phenytoin, lamotrigine, phenobarbital are associated with high risk for occurrence of TEN. We present a case of toxic epidermal necrolysis in a 30 year old female probably induced by phenytoin. A 30 year old female was admitted to the emergency medicine department of KIMS hospital, Bengaluru. Lesions over the lips and oral cavity, multiple fluid filled blisters were present diffusely all over the body. Patient had a past history of oral cavity lesions with injection phenytoin. Patient is a known epileptic of over 12 years and was on treatment. Patient had a seizure attack 3 days back and visited nearby hospital and did not inform the doctor of her allergy to phenytoin. Patient was given inj phenytoin after which she developed oral lesions and also presented with fluid filled bullae all over the body. A diagnosis of toxic epidermal necrolysis was made based on clinical history and Scoreten score and was treated with betadine wash, fluconazole and antibiotics .The lesions improved significantly with the above management and patient recovered enough to be discharged from the hospital after 5 days. Severe and serious reactions such as toxic epidermal necrolysis can be caused by commonly used drugs like phenytoin.